Solar thermo-chemical process assisting a pressure oxidation process for co-production of electricity and metal - Behar, Omar; Sbarbaro, Daniel; Moran, Luis (جامعة الوادي - university of el oued, 2021)
The mining industry is looking at the use of solar energy to address issues related to highly variable energy prices, falling ore grades, and increasing concern about the industry’s carbon footprint. The pressure oxidation of ore sulfides is an economic alternative to the smelting process because it has the potential to reduce energy consumption and treat low-grade ores. In the pressure oxidation of ore sulfides, the purity and utilization of oxygen are key factors. Indeed, oxygen production and consumption constitute the major operating cost of the pressure oxidation process. Solar thermo-chemical looping processes have been identified as one of the most efficient pathways for the production and storage of oxygen. This study investigates the integration of a solar thermo-chemical looping process with a pressure oxidation process to treat ore sulfide and produce electricity. The analysis shows that the temperature of the cold storage tank has a strong influence on the performance of the complete system. The increase in the cold tank temperature results in a sharp decrease in the size of the receiver. This reduce the investment costs for both the solar receiver and the heliostat field. For the considered case, the useful heat of the solar receiver is 3.7 MWth when the cold tank temperature is set at 100°C. If the cold tank temperature is set at 400°C, the required useful solar heat is about 3.1 MWth and the nominal output of the gas turbine is 0.56 MWe. The analysis showed that about 80% of the useful solar heat can be used to generate oxygen when the temperature of the cold tank is as high as that of the reduction reaction.
Article
Keywords: Solar thermo-chemical, pressure oxidation, energy storage, oxygen production, oxidation / reduction, solar mining process